The Effect Of Environmental, Social, and Governance (ESG) Pillars and State Ownership on Firm Costs of Debt - Fery Perdiansyah; Maria Ulpah (UNIVED Press, 2024)
The relevance of environmental, social, and governance (ESG) factors has become increasingly significant in the business world due to the growing recognition of sustainability principles. This study investigates the impact of ESG pillars and state ownership on the cost of debt in non financial companies. The analysis is conducted on publicly listed firms in emerging Asian countries over the period 2016 to 2023, using panel data regression. Drawing on various theories such as agency theory, stakeholder theory, and signaling theory, the research demonstrates that state owned enterprises with higher ESG scores incur lower debt costs. Another finding is that the social pillar positively influences debt costs. Although the environmental pillar is negatively associated with debt costs, its impact is not significant. Meanwhile, the governance pillar has a significant negative effect on debt costs, consistent with agency theory. The results of this study are expected to provide insights for stakeholders, particularly managers and company owners, regarding the role of ESG and state ownership in determining firm cost of debt.